The Need to Update Endpoints and Outcome Analysis in the Rapidly Changing Field of Liver Transplantation. Issue 5 (9th November 2021) - Fodor, Margot; Zoller, Heinz; Oberhuber, Rupert; Sucher, Robert; Seehofer, Daniel; Cillo, Umberto; Line, Pal Dag; Tilg, Herbert; Schneeberger, Stefan
Abstract : Liver transplantation (LT) survival rates have continued to improve over the last decades, mostly due to the reduction of mortality early after transplantation. The advancement is facilitating a liberalization of access to LT, with more patients with higher risk profiles being added to the waiting list. At the same time, the persisting organ shortage fosters strategies to rescue organs of high-risk donors. This is facilitated by novel technologies such as machine perfusion. Owing to these developments, reconsideration of the current and emerging endpoints for the assessment of the efficacy of existing and new therapies is warranted. While conventional early endpoints in LT have focused on the damage induced to the parenchyma, the fate of the bile duct and the recurrence of the underlying disease have a stronger impact on the long-term outcome. In light of this evolving landscape, we here attempt to reflect on the appropriateness of the currently used endpoints in the field of LT trials.